Strukturalisme Tzevan Todorov Pada Cerpen Qismati wa Nasibi Karya Najib Mahfuz - Perdana, Dyah Adila (Journal of Arabic Language Studies and Teaching, 2025)
This article analyses the short story "Qismati dan Nasibi" by Najib Mahfuz to explore the narrative structure within the story using Tzvetan Todorov's structuralist semiotic approach. The study employs a descriptive-qualitative method, with data collected and classified through active reading techniques. The results of the active reading were then analysed using discourse analysis based on Todorov's structuralist semiotic approach. The findings reveal that Todorov's analysis of literary works consists of three main aspects: (1) the syntactic aspect, which focuses on the structural composition of the narrative; (2) the semantic aspect, which is divided into syntagmatic and paradigmatic relations that reveal meaning through textual connections; and (3) the verbal aspect, which includes narrative mode, tense, point of view, story type, and narrator. By analysing the textual elements, including words and sentences, that reflect these three aspects, the study identifies the fundamental structure that constructs the overall meaning of the work.